The Journalism Today / Workbook: Learning Activities for Tomorrow's Journalists - Ferguson Donald L; Patten Jim (National Textbook Company, 1988)
This book is designed to help students practice and develop basic journalistic skills. Introduction, Learning Style, Considering Law and Ethics, Working on News Judgement, Doing Interviews, Writing Leads, Writing New Stories, Using Quotes, Covering Speeches, Writing Feature Stories, Writing Sports Stories, Writing Editorials, Writing Headlines, Using Photos Effectively, Writing for Broadcast, Creating Ads, Planning the Yearbook, Brainstorming Technique, Copy Editing Symbols.